2009
DOI: 10.1159/000204108
|View full text |Cite
|
Sign up to set email alerts
|

Corr4A and VRT325 do not Reduce the Inflammatory Response to <i>P. aeruginosa</i> in Human Cystic Fibrosis Airway Epithelial Cells

Abstract: Background: P. aeruginosa chronically colonizes the lung in CF patients and elicits a proinflammatory response. Excessive secretion of IL-6 and IL-8 by CF airway cells in response to P. aeruginosa infection in the CF airway is though to contribute to lung injury. Accordingly, the goal of this study was to test the hypothesis that Corr4a and VRT325, investigational compounds that increase ΔF508-CFTR mediated Cl- secretion in human CF airway cells, reduce the pro-inflammatory response to P. aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…CFBE41o-cells treated with either VRT-325 or Corr4a, two investigational compounds that increase F508del-CFTR chloride secretion, failed to show improvement in IL-6 or IL-8 concentrations after exposure to P aeruginosa. 50 In a subsequent study, neither to stimulate phagocytosis and killing of P aeruginosa by macrophages. 54 The fact that the inflammatory response in cells isolated from people with CF and studied ex vivo was attenuated by the administration of CFTR modulators indicates that CF inflammation is not entirely effective or beneficial, but it may be related to the underlying basic defect.…”
Section: S33mentioning
confidence: 90%
See 1 more Smart Citation
“…CFBE41o-cells treated with either VRT-325 or Corr4a, two investigational compounds that increase F508del-CFTR chloride secretion, failed to show improvement in IL-6 or IL-8 concentrations after exposure to P aeruginosa. 50 In a subsequent study, neither to stimulate phagocytosis and killing of P aeruginosa by macrophages. 54 The fact that the inflammatory response in cells isolated from people with CF and studied ex vivo was attenuated by the administration of CFTR modulators indicates that CF inflammation is not entirely effective or beneficial, but it may be related to the underlying basic defect.…”
Section: S33mentioning
confidence: 90%
“…Studies in CF cell models have attempted to determine whether pharmacologic improvement of CFTR function alters the inflammatory response. CFBE41o‐cells treated with either VRT‐325 or Corr4a, two investigational compounds that increase F508del‐CFTR chloride secretion, failed to show improvement in IL‐6 or IL‐8 concentrations after exposure to P aeruginosa . In a subsequent study, neither VX‐809 (lumacaftor) nor VX‐809 in combination with VX‐770 (lumacaftor/ivacaftor) reduced IL‐8 or IL‐6 secretion in CFBE41o‐ or CF‐human bronchial epithelial cells (HBE) cells at baseline or after stimulation with P aeruginosa .…”
Section: Associations Between Abnormal Cftr and Airway Inflammationmentioning
confidence: 99%
“…It was shown to have an effect on stabilizing ΔF508-CFTR, leading to increased channel function [58]. Although, Talebian et al have recently shown that VRT-532, and another potential corrector drug, Corr4A, do not reduce the IL-6 and IL-8 inflammatory response in CFBE41o- cells [59]. Thus, these drugs will likely have little effect on reversing the chronic lung disease.…”
Section: Pharmacological Therapeutic Strategies To Correct Cftr Protementioning
confidence: 99%
“…Ussing chamber measurements of Phe508del-CFTR Cl Ϫ currents. As described in detail elsewhere (31,32,35), cells on Snapwell filters were mounted in Ussing chambers. CF HBEC or CFBE cells were treated with vehicle, HP␤CD (5 mM), or M␤CD (5 mM) (Sigma) on the apical side or basolateral side of monolayers.…”
Section: Methodsmentioning
confidence: 99%